TENSILE STRENGTH STUDY OF UNSATURATED POLYESTER /POLYVINYL CHLORIDE COMPOSITES REINFORCED WITH GLASSFIBERS - Jawad, Mohamed; Majeed, Kawakib; Al-Ajaj, Ekram (Iraqi Journal of Science, 2024)
Tensile strength study of UPE/PVC composites reinforced with one and two layers ofrandom glass fibers has been investigated. Hand lay up method was used to preparesheets of UPE/PVC blends with different weight percentage of PVC(10%,20% and30%)Results show increasing in the values of maximum stresses, yield stresses and modulusof elasticity for UPE/PVC blends with increasing the weight percentage of the polyvinylchloride (PVC) . UPE/PVC blends reinforced with one layer of glass fiber results showgood mechanical properties for the composite which contain 20% PVC. Also the resultsshow that composites reinforced with two layers of glass fiber randomly increasing invalues of maximum stresses with increasing PVC percentage .